​​Pengaruh G96 dan G97 terhadap Kekasaran Permukaan ST 37 dan S45C pada Pembubutan CNC​ - pujo leksonowati, nur fitria; Pamungkas, Nurman; Baharudin, Budi; Cahyagi, Danang; Van Gunawan, Leo; Adimas, Adimas (Journal of Applied Mechanical Technology, 2025)
ABSTRACT – This study aims to compare the effects of Constant Cutting Speed (G96) and Constant Spindle Speed (G97) modes on the surface roughness of ST 37 and S45C materials in step-turning processes using a CNC lathe. A comparative experimental method was employed, measuring surface roughness (( R_a )) at stepped diameters (16 mm, 24 mm, 32 mm, and 35 mm) with a Mitutoyo Surface Tester SJ-210. Results indicate that G96 mode produces lower surface roughness, with average ( R_a ) values of 2.22 µm (S45C) and 2.27 µm (ST 37) in the N6 class, compared to G97 mode with ( R_a ) values of 3.08 µm (S45C) and 3.03 µm (ST 37) in the N7 class. G96 mode is superior due to its ability to automatically adjust rotational speed based on diameter, whereas in G97 mode, small diameters with high rotation (1273 rpm) increase roughness due to vibration or heat. This study recommends using G96 mode for optimal surface smoothness in step-turning of similar materials. rning of similar materials.